THE EFFECTIVENESS OF ACCEPTANCE AND COMMITMENT THERAPY (ACT) TECHNIQUES IN COUNSELING TO REDUCE AGGRESSION BEHAVIOR: LITERATURE REVIEW - Juni Fajar Sari; Eka Wahyuni; Karsih Karsih (LP2M IAI Al-Khairat Pamekasan, 2025)
This article reports the results of a systematic review of articles published between 2020 and 2025 that specifically examine the effectiveness of Acceptance and Commitment Therapy (ACT) techniques in counseling to reduce aggressive behavior. The databases used are Semantic Scholar, PubMed, and DOAJ. Articles selected from various databases use the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. The results of the analysis of five selected articles revealed that ACT is effective in reducing aggressive behavior in both school and college students. When compared to Beck cognitive therapy and CBT, ACT is more effective in reducing aggressive behavior. In ACT therapy sessions, clients' feelings of anger, hostility and all types of verbal and physical aggression are accepted and the feelings associated with them are expressed and adjusted in feedback with group members. If the client's negative feelings are softened during the ACT therapy session, and if they recognize their personal values ​​and turn them into desired behavioral goals, then mental peace will be achieved, thereby reducing aggressive behavior. The results of this study support the use of ACT as an effective approach to help students reduce their aggressive behavior in a more adaptive manner.